The Influence of Financial Accounting Implementation on the Operational Efficiency of Ninja Express Warehouse in Solo City - Pratama, Yogie; Abdul Gani; Minasari Nasution (Sean Institute, 2025)
This study aims to analyze the effect of financial accounting implementation on the operational efficiency of the Ninja Express warehouse in Solo City. In the highly competitive logistics industry, operational efficiency is a key factor in improving service quality, delivery speed, and customer satisfaction. Proper implementation of financial accounting is expected to provide accurate, relevant, and timely information that can assist management in planning, controlling, and evaluating warehouse operational activities. The research method employed is a quantitative approach with data collection techniques including questionnaires, interviews, and documentation. Respondents consist of finance staff, operational managers, and warehouse employees. The observed variables include transaction recording systems, financial reporting, and internal control mechanisms. The results of the study indicate that the implementation of financial accounting has a significant positive effect on the operational efficiency of Ninja Express warehouses. A well-structured accounting system reduces the risk of recording errors, minimizes cost inefficiencies, accelerates information flow, and improves the accuracy of planning and performance evaluation. These findings confirm that financial accounting does not only function as a recording tool but also serves as a strategic instrument in supporting the sustainability and competitiveness of logistics companies, particularly amidst the growing demand for delivery services. Furthermore, this research highlights the importance of integrating financial accounting with digital systems and warehouse management technology. The synergy between accounting practices and digital platforms can optimize resource utilization, strengthen decision-making processes, and enhance overall organizational performance. This suggests that companies in the logistics sector should continuously adapt their accounting systems to technological developments in order to maintain efficiency and remain competitive in a dynamic business environment.